Fishing for MSY: using "pretty good yield" ranges without impairing recruitment. (25th June 2016) - Rindorf, Anna; Cardinale, Massimiliano; Shephard, Samuel; De Oliveira, José A. A.; Hjorleifsson, Einar; Kempf, Alexander; Luzenczyk, Anna; Millar, Colin; Miller, David C. M.; Needle, Coby L.; Simmonds, John; Vinther, Morten
Abstract : Pretty good yield (PGY) is a sustainable fish yield corresponding to obtaining no less than a specified large percentage of the maximum sustainable yield (MSY). We investigated 19 European fish stocks to test the hypothesis that the 95% PGY yield range is inherently precautionary with respect to impairing recruitment. An F MSY range was calculated for each stock as the range of fishing mortalities ( F ) that lead to an average catch of at least 95% of MSY in long-term simulations. Further, a precautionary reference point for each stock ( F P.05 ) was defined as the F resulting in a 5% probability of the spawning-stock biomass falling below an agreed biomass limit below which recruitment is impaired ( B lim ) in long-term simulations. For the majority of the stocks analysed, the upper bound of the F MSY range exceeded the estimated F P.05 . However, larger fish species had higher precautionary limits to fishing mortality, and species with larger asymptotic length were less likely to have F MSY ranges impairing recruitment. Our study shows that fishing at F MSY generally is precautionary with respect to impairing recruitment for highly exploited teleost species in northern European waters, whereas the upper part of the range providing 95% of MSY is not necessarily precautionary for small- and medium-sized teleosts.